Forensic Determination of the Worth of Cultural Property - A. Ya. Asnis; S. N. Khaziev (Теория и практика судебной экспертизы, 2021)
Forensic determination of the worth of various objects involved in legal proceedings is essential for ensuring a fair trial. Determining the worth of mass-produced goods does not usually pose any diﬃculties. The situation is diﬀerent for unique cultural values and items that are in particular demand among collectors, history buﬀs, and others, but are withdrawn from civil circulation for moral reasons.The article analyzes the most signiﬁcant aspects of the current market of cultural values, considers the methodological foundations of the forensic assessment of the worth of cultural values, mainly works of ﬁne and applied art. The authors substantiate the necessity for a comprehensive forensic examination of cultural values due to the requirement for preliminary identiﬁcation of the authenticity of items, their author, circumstances, and time of creation. The types of research necessary for this have been identiﬁed, such as traceological, documentary, materials analysis, historical, art, and others.The paper shows that forensic assessment of the worth of the items withdrawn from civil circulation based on the data on their worth on the black (illegal) market or on the legal markets of countries where the circulation of such items is not legally prohibited is inadmissible. The prohibition on using information about events that occurred after assessing the worth of cultural property is substantiated.